Slavic Morphemics in Comparative Studies - Карпіловська, Євгенія А. (Języki słowiańskie dziś: w kręgu kategorii, struktur i procesów, 2021)
The comparative study of Slavic morphemics is essential for expanding knowledge on such issues as the typology of the structure of Slavic words and its nature, the resources of Slavic nomination (first of all, morphological word-formation), the modes of adaptation of borrowings, and the semantic potential of morphemic resources of Slavic languages (semantic word-formation). This approach focuses on morphemics as a set of means of forming the morphemic structure of a word in a Slavic language and forming Slavic words in general. Such means constitute the morphemic system of a language. At the lower level there are separate morphemes of different classes (roots, affixes, flexions, interfixes). Higher levels of the system consist of complex units – morphemic combinations of different types (affixal pairs and chains, affixal lattices or affix-root combinations, morphemic word structures, morphemic networks of parts of speech). Considering that work on the description of morphemes in modern Slavic languages is at various stages of progress, in order to provide the basis for the development of standards of comparison it is reasonable to examine available descriptions of individual morphemes and compare the range of their formal, semantic and functional features presented in existing morphemic dictionaries of Slavic languages. A comparison of these dictionaries reveals inconsistencies both in terms of description of morphemes, their form, semantics and function in the word, and in terms of how they are presented. This stems from different types of morphemic analysis applied and from the traditions of interpreting the results in particular Slavic languages. It is possible to eliminate such inconsistencies by comparing morphemes with a common form and semantics for genetically related units, and comparing only semantics for units with a different form and origin. The comparative study of individual morphemes will provide a basis for comparing complex morphemic units and morphemic systems of modern Slavic languages in general. The results will make it possible to gain more in-depth knowledge on the typical and distinctive use of morphemic resources of these languages to create a word as the basic unit of their nomination.